How perceived support relates to child autism symptoms and care-related stress in parents caring for a child with autism. (April 2019) - Goedeke, Sonja; Shepherd, Daniel; Landon, Jason; Taylor, Steve
Highlights: Parents report higher levels of support from their partners/family than other sources. Support did not affect parents' assessment of children's symptoms. Partner support affected care-related stress associated with particular symptoms. Professional support was related to lower care-related stress. Abstract: Background: Caring for a child with autism spectrum disorder (ASD) may be stressful and subsequently affect parents' ability to manage their child's symptoms. In this research, we explore the effects of perceived levels of support on parents' care-related stress and on ASD symptoms. Method: Participants (n = 585) completed an online survey which included ratings of support (partner, family, friend, professionals), how they perceived their child's symptoms, their care-related stress, and ratings of their child's interventions. Results: Results indicate that parents perceive partners and families as providing greater support than friends and professionals. However, perceptions of family support decrease with both parent and child age. Perceived family support did not appear to influence parents' perceptions of their child's symptoms, although partner support moderated the relationship between particular symptom subsets and care-related stress. Professional support was related to a decrease in care-related stress levels. Finally, some sources of support were associated with perceived effectiveness and stress reduction in relation to specific interventions. Conclusions: Partners and family provide an important support role for parents yet may need education and support to assist them in this role on an ongoing basis. Understanding how professionals can better support parents in their caregiving role is also important.